Are Numbers or Words the Key to User Reliance on AI? - Papenkordt, Jörg; Ngonga-Ngomo, Axel-Cyrille; Thommes, Kirsten (Academy of Management Proceedings)

Putting Data Privacy Regulation into Action: The Differential Capabilities of Service Frontline Interfaces - Steinhoff, Lena; Martin, Kelly D. (Journal of Service Research)
Service frontline encounters between customers and service providers have been subject to fundamental changes in recent years. As two major change agents, technology infusion and data privacy regulations are inextricably linked and constitute a critical ethical and societal issue. Specifically, service frontlines—as represented by human or technological agents, or some hybrid form—rely on customer data for service provision, which subjects them to privacy regulations governing the collection, submission, access, and use of any customer data thus captured. However, scant research outlines the significant implications of evolving data privacy regulations for service frontline encounters. To advance knowledge in this domain, this research distills six key dimensions of global data privacy regulations (fairness, data limits, transparency, control, consent, and recourse). Employing an intelligences theoretical lens, the authors theorize how these dimensions might become differentially manifest across three service frontline interface types (human-based, technology-based, and hybrid). Carefully intersecting the need for varying intelligences across data privacy regulatory dimensions with the abilities of service frontline interfaces to harness each intelligence type, this study offers a novel conceptual framework that advances research and practice. Theoretical, managerial, and policy implications unfold from the proposed framework, which also can inform a future research agenda.
Keywords: Organizational Behavior and Human Resource Management; Sociology and Political Science; Information Systems

Belastungsgerechte Auslegung automobiler Leichtbaustrukturen aus pressgehärtetem Stahl und kohlenstofffaserverstärktem Kunststoff - Triebus, Marcel
Hybride Bauteile, welche aus Werkstoffen mit hohen spezifischen Festigkeiten bestehen, können zu einem signifikanten Leichtbau im Automobil beitragen. Diese Arbeit erforscht die hybride Kombination von pressgehärtetem Stahl und kohlenstofffaserverstärktem Kunststoff. Ausgehend von einer Analyse bestehender Karosseriestrukturen erfolgt ein Konzept für eine hybride B-Säule. Das Potential zur Gewichtsreduzierung durch das hybride Bauteilkonzept wurde dabei zu 57 % identifiziert, welches jedoch nur bei Sicherstellung einer intakten Grenzfläche erreicht wird. Zur Erlangung der Grenzflächenfestigkeit bei charakteristischen Belastungsprofilen wurde ein Verfahren zur Einbringung makroskopischer Formschlusselemente im Presshärteprozess entwickelt. Durch diese Formschlusselemente wird eine Steigerung der Scherfestigkeit der hybriden Komponenten von über 300 % erreicht. Die gewonnenen Erkenntnisse werden abschließend zur Auslegung einer hybriden B-Säule angewendet.

Primary school teachers’ perspectives on the quality of inclusive education - Görel, Gamze; Franzen, Katja; Hellmich, Frank (Teachers and Teaching)
Keywords: Arts and Humanities (miscellaneous); Education

Zwischen lebensunwertem und selbstbestimmtem Leben. Impulse des 20. Jahrhunderts für eine ableismuskritische Religionspädagogik - Neumann, Anna (Katastrophen. Religiöse Bildung angesichts von Kriegs- und Krisenerfahrungen im 19. und 20. Jahrhundert)

Jesus heilt. Warum nicht alle? Heilungswunder aus der Perspektive von Menschen mit Behinderung - Neumann, Anna; Kammeyer, Katharina (Religion 5-10)

The Importance of Distrust in AI - Peters, Tobias Martin; Visser, Roel W. (Communications in Computer and Information Science)

From European Symbolism to German Gesture: The International and Transnational Nationalism of Stefan George’s Blätter für die Kunst - Gretz, Daniela (German Literature as a Transnational Field of Production, 1848-1919)

Conceptual understanding of third grades for axial symmetry - Wallner, Melina; Häsel-Weide, Uta (International Symposium in Elementary Mathematics Teaching. Proceedings: New Directions in Elementary Mathematics Education)

Employer Branding - Wie Arbeitgeber strategisch gegen den Arbeitskräftemangel vorgehen. - Schneider, Martin; Radermacher, Katharina (Die Politische Meinung)

Transformationen des Faktualen. Darstellungsstrategien multimodalen Erzählens in der biografischen Graphic Novel "Guantanamo Kid. Die wahre Geschichte des Mohamed al Gharani" - Böker, Ines; Willeke, Stephanie (Literatur im Unterricht. Texte der Gegenwartsliteratur für die Schule. Krieg. Repräsentationen in Literatur und Medien der Gegenwartsliteratur.)

(Ver-)störendes Held*innentum. Figurationen und Repräsentationen von Soldatinnen und Soldaten in postheroischen Kriegszeiten - Böker, Ines (Limbus. Australisches Jahrbuch für germanistische Literatur und Kulturwissenschaft)

Nachhaltigkeit in der Bildung fOERdern: Open Educational Resources in der Hochschullehre - Weber, Tassja (Inverted Classroom and beyond 2023: Agile Didaktik für nachhaltige Bildung)

A model of cycles and bubbles under heterogeneous beliefs in financial markets - Burs, Carina (Cogent Economics & Finance)
I study the effect of heterogeneous beliefs about asset prices on the long-term behavior of financial markets. Starting from the ideas of Abreu and Brunnermeier (Citation2003), a two-dimensional system of differential equations is developed. The first dynamic variable is the asset price growth rate. The second dynamic variable is the number of investors who believe that asset prices are abnormally high. In a phase plane analysis, I find both stable and unstable equilibria, depending on the spread of information and the response to other agents’ beliefs. If individuals try to increase their returns while perceiving more overpricing, these equilibria can be spirals or even approach limit cycles. Although I intend to study general price patterns, abnormally high asset prices can be caused by financial bubbles. In this model, bubbles can emerge and deflate both in cycles or directly, or they can grow until they burst. Further, I analyze market behavior after a central bank increases the interest rate. This can lead to new stable equilibria, but the emergence and bursting of bubbles cannot be prevented.
Keywords: asset pricing; subjective information; stability conditions; monetary policy; risk aversion

Die Fremdheit der Tiere. Zur theologischen Konstruktion und Dekonstruktion des Anderen - Herdramm, Henrike

Die Tiervergessenheit in der Theologie - Herdramm, Henrike (Feinschwarz.net)
Keywords: Tiertheologie; Tiervergessenheit; Anthropozentrismus

Die Tiertheologie und die Schöpfungstheologie - Herdramm, Henrike

Nachhaltigkeit durch Daten im MBSE: Einblick in die Entwicklung eines Modell-Empfehlungssystems - Tissen, Denis; Tschirner, Christian; Koldewey, Christian; Dumitrescu, Roman (Tag des Systems Engineering)

Uncool cowboys in low-low-land? Public perception and aesthetics of the German country music scene. - Jacke, Christoph; Kirschlager, Nils (Beyond Style and Genre. Aesthetic Concepts in Popular Culture.)

A process-model for tailoring prototyping of cyber-physical systems - Tissen, Denis; Koldewey, Christian; Dumitrescu, Roman

Hypernetworks: Cluster Synchronization Is a Higher-Order Effect - von der Gracht, Sören; Nijholt, Eddie; Rink, Bob (SIAM Journal on Applied Mathematics)
Many networked systems are governed by non-pairwise interactions between nodes. The resulting higher-order interaction structure can then be encoded by means of a hypernetwork. In this paper we consider dynamical systems on hypernetworks by defining a class of admissible maps for every such hypernetwork. We explain how to classify robust cluster synchronization patterns on hypernetworks by finding balanced partitions, and we generalize the concept of a graph fibration to the hypernetwork context. We also show that robust synchronization patterns are only fully determined by polynomial admissible maps of high order. This means that, unlike in dyadic networks, cluster synchronization on hypernetworks is a higher-order, i.e., nonlinear, effect. We give a formula, in terms of the order of the hypernetwork, for the degree of the polynomial admissible maps that determine robust synchronization patterns. We also demonstrate that this degree is optimal by investigating a class of examples. We conclude by demonstrating how this effect may cause remarkable synchrony breaking bifurcations that occur at high polynomial degree.
Keywords: Applied Mathematics

Lawrence Grossberg (2019): Pessimismus des Willens, Optimismus des Verstands. Schlussstriche und Neuanfänge. Hrsg. von Roman Horak. Wien und Berlin: Turia + Kant; Roman Horak (2019): Jenseits der Kulturwissenschaften. Beiträge zu Cultural Studies, Popular- und Massenkultur. Wien: Löcker; Jürgen Mittelstraß (2020): Leonardo-Welten. Zwischen Kunst und Wissenschaft. Weilerswist: Velbrück Wissenschaft; Jürgen Mittelstraß (2021): Fröhliche Wissenschaft? Philosophische Grenzgänge zwischen Wissenschaft und Gesellschaft. Weilerswist: Velbrück Wissenschaft. - Jacke, Christoph (Testcard. Beiträge zur Popgeschichte. Rechtspop.)

Martha and Her Sister(s) – Female Voices in the Fourth Gospel - Taschl-Erber, Andrea (More than Female Disciples: An Examination of Women’s Authority in Ancient Christianity (Ist-VIth centuries))

Making “the Two” Into One Body: De- and Recategorization of (Un-) Circumcision - Taschl-Erber, Andrea (Reconsidering the Letter to the Ephesians in Context (Wissenschaftliche Untersuchungen zum Neuen Testament))

(K)ein Ende des „Alten Bundes“? Paulinische Schrifthermeneutik in 2 Kor 3 - Taschl-Erber, Andrea (Heilige Texte. Verständigungen zwischen Theologie und Kulturwissenschaft)

The influence of effort instructions on fake production costs in basketball novices and experts - Böer, Nils Tobias; Güldenpenning, Iris; Weigelt, Matthias (Abstracts of the 55th Autumn Meeting of Experimental Cognitive Psychology (HExKoP))
Keywords: action preparation; perception; movement planning; deception

Adaptation to context information for head fakes in basketball - Güldenpenning, Iris; Böer, Nils Tobias; Kunde, Wilfried; Weigelt, Matthias (Abstracts of the 65th Conference of experimental Psychologists (TeaP))

Wissenschaft und Alltagserfahrung: Überlegungen zur Wissenschaftsdidaktik der Psychologie - Scharlau, Ingrid (Wissenschaftsdidaktik II: Einzelne Disziplinen)
Keywords: Unterrichtsfach Psychologie

Die Nutzung von (Evidenz-)Quellen im Referendariat - Homt, Martina; Bloh, Bea

Private Set Intersection using Third Generation FHE - Anonymous, A.

Rational Models in Cryptography Applied to Matching - Anonymous, A.

Medienästhetik und dann? - Bartz, Christina (Medienkritik und Wirkungsästhetik. Konvergenzen und Zuschreibungen schädlicher und wünschenswerter Rezeptionseffekte von Literatur und Medien seit dem 18. Jahrhundert)

Platform Approach for Modularising Battery Electric fast Ferries - Seidenberg, Tobias; Disselkamp, Jan-Philipp; Jürgenhake, Christoph; Anacker, Harald; Dumitrescu, Roman; Papanikolaou, Apostolos (Proceedings of the Design Society)
Abstract The transportation sector is responsible for a relevant share of the total emissions and offers great potentials. It is necessary to implement as many zero-emission mobility systems as possible in the shortest time. For fast ferries, which are a relevant transport manner for a large share of the global population, technical issues could be solved and the successful operation was demonstrated. Up to today high-speed ships have been fully individually designed because physical effects demand for an individual optimisation for each use-case. Specifically for battery electric ships the overall efficiency is crucial to ensure not only an ecological but also economical operation. With today's methods the design and production of such an individual designed ferry does take too long. To cover the rising demand, new approaches for mass production need to be established. In this paper we describe a method for designing a platform for ships with the example of a battery electric fast ferry. The focus is on the actual modularisation, as other aspects like requirements or results of our example case are published elsewhere and are therefore just included briefly. The method is validated on the world's first battery powered high-speed ferry.

A systematic literature review on the Digital Twin of the factory in the context of the product and factory lifecycle - Cieply, Jonas; Disselkamp, Jan-Philipp; Dyck, Florian; Alturk, Waddah; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Development of a modular architecture for complex mechatronic systems - Seidenberg, Tobias; Disselkamp, Jan-Philipp; Jürgenhake, Christoph; Grobbel, Daniel; Dumitrescu, Roman; Papanikolaou, Apostolos (Procedia CIRP)
Keywords: General Medicine

Integrated product and production development - a systematic literature review - Disselkamp, Jan-Philipp; Cieply, Jonas; Dyck, Florian; Grothe, Robin; Anacker, Harald; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Systems Engineering Potentials and Use Cases for the Offer Phase in Special Purpose Machinery - Wilke, Daria; Humpert, Lynn; Mansheim, Johanna; Anacker, Harald; Dumitrescu, Roman (DS 125: Proceedings of the 34th Symposium Design for X (DFX2023))

Venture Client Model: A systematic Literature Review - Haarmann, Lennard; Machon, Fabian; Rabe, Martin; Asmar, Laban; Dumitrescu, Roman (European Conference on Innovation and Entrepreneurship)
Established companies are increasingly opening their innovation systems to stay ahead of the competition. In this context, collaboration with innovative and agile start-ups are gaining continuously more importance. In the past established companies often used common corporate venturing methods such as incubators, accelerators, or corporate venture capital for collaboration. Compared to these methods the venture client model is relatively new and was invented by BMW employees in 2014. Using the venture client model, established companies become early clients of the start-ups even it is still a venture to do so. Together they carry out a pilot project to develop a proof of concept and validate it under real conditions. If successful, they enter a long-term collaboration to integrate the start-up’s solution into products, processes, or business models of the established company. The aim of this paper is to sum up the current literature and set a foundation for future research on this topic. Therefore, we conduct a systematic literature review. As a result, we provide a definition of the venture client model, describe characteristics, present advantages from the perspective of established companies and start-ups. In addition, we summarize the state of research regarding strategy, process, and organizational structure and for the venture client model. In terms of strategy, future research should elaborate defining elements of a strategy as well as ways to integrate the venture client model into the corporate innovation-ecosystem. Focusing on the process additional research is needed on a venture client reference process and its integration into the corporate’s core processes. Referring to the organizational structure a reference architecture for a venture client unit as well as its positioning within the organization (e.g., innovation management or corporate strategy) should be further investigated.

Framework for Dual Transformation: A Systematic Literature Review on the Interplays between Digitalization and Sustainability - Kürpick, Christian; Kühn, Arno; Olszewski, Luca; Dumitrescu, Roman (2023 IEEE Conference on Technologies for Sustainability (SusTech))

A Technology Foresight Maturity Model - Ellermann, Kai; Asmar, Laban; Dumitrescu, Roman (ISPIM Conference Proceedings)

A process mining maturity model: Enabling organizations to assess and improve their process mining activities - Brock, Jonathan; Löhr, Bernd; Brennig, Katharina; Seger, Thilo; Bartelheimer, Christian; von Enzberg, Sebastian; Kühn, Arno; Dumitrescu, Roman (ECIS 2023 Proceedings at AIS Electronic Library (AISeL).)

It’s like flossing your teeth: On the Importance and Challenges of Reproducible Builds for Software Supply Chain Security - Fourné, Marcel; Wermke, Dominik; Enck, William; Fahl, Sascha; Acar, Yasemin (2023 IEEE Symposium on Security and Privacy (SP))

PEA: core-analogue for non-cohesive games - Aslan, Fatma; Duman, Papatya; Trockel, Walter (Economics Bulletin)

Time-resolved pump–probe spectroscopic ellipsometry of cubic GaN. I. Determination of the dielectric function - Baron, Elias; Goldhahn, Rüdiger; Espinoza, Shirly; Zahradník, Martin; Rebarz, Mateusz; Andreasson, Jakob; Deppe, Michael; As, Donat Josef; Feneberg, Martin (Journal of Applied Physics)
An ultra-fast change of the absorption onset for zincblende gallium-nitride (zb-GaN) (fundamental bandgap: 3.23 eV) is observed by investigating the imaginary part of the dielectric function using time-dependent femtosecond pump–probe spectroscopic ellipsometry between 2.9 and 3.7 eV. The 266 nm (4.66 eV) pump pulses induce a large electron–hole pair concentration up to 4×1020cm−3, which shift the transition energy between conduction and valence bands due to many-body effects up to ≈500 meV. Here, the absorption onset increases due to band filling while the bandgap renormalization at the same time decreases the bandgap. Additionally, the absorption of the pump-beam creates a free-carrier profile within the 605 nm zb-GaN layer with high free-carrier concentrations at the surface, and low concentrations at the interface to the substrate. This leads to varying optical properties from the sample surface (high transition energy) to substrate (low transition energy), which are taken into account by grading analysis for an accurate description of the experimental data. For this, a model describing the time- and position-dependent free-carrier concentration is formulated by considering the relaxation, recombination, and diffusion of those carriers. We provide a quantitative analysis of optical experimental data (ellipsometric angles Ψ and Δ) as well as a plot for the time-dependent change of the imaginary part of the dielectric function.
Keywords: General Physics and Astronomy

Frühe Versuche zur Etablierung des Hochschulstandorts Paderborn (1945-1970) - Grüttner, Niclas Christian (50 Jahre Universität Paderborn. Studentische Forschungsprojekte zur Gründungsgeschichte. Ein Rückblick)

Evaluation of the Influence of Different Energy Usage Behavior, Component Dimensionings and PV Orientations on the Suitability and Lifetime of a Hybrid, Hydrogen-Based PV Energy System for a Private Household - Möller, Marius Claus; Krauter, Stefan (Proceedings of the 40th European Photovoltaik Solar Energy Conference and Exhibition)

PV Microinverters: Latest Efficiency Rankings, Energy Yield Assessments, Firmware Issues - Krauter, Stefan; Bendfeld, Jörg (Proceedings of the 40th European Photovoltaik Solar Energy Conference and Exhibition)

Lifelogging in einer Kultur der Digitalität. Analysen aus der medienkompetenztheoretischen Perspektive Dieter Baackes. - Dehmel, Lukas; Burgfeld-Meise, Bianca (Ludwigsburger Beiträge zur Medienpädagogik)

Vibrational Properties of the Potassium Titanyl Phosphate Crystal Family - Neufeld, Sergej; Gerstmann, Uwe; Padberg, Laura; Eigner, Christof; Berth, Gerhard; Silberhorn, Christine; Eng, Lukas M.; Schmidt, Wolf Gero; Rüsing, Michael (Crystals)
The crystal family of potassium titanyl phosphate (KTiOPO4) is a promising material group for applications in quantum and nonlinear optics. The fabrication of low-loss optical waveguides, as well as high-grade periodically poled ferroelectric domain structures, requires a profound understanding of the material properties and crystal structure. In this regard, Raman spectroscopy offers the possibility to study and visualize domain structures, strain, defects, and the local stoichiometry, which are all factors impacting device performance. However, the accurate interpretation of Raman spectra and their changes with respect to extrinsic and intrinsic defects requires a thorough assignment of the Raman modes to their respective crystal features, which to date is only partly conducted based on phenomenological modelling. To address this issue, we calculated the phonon spectra of potassium titanyl phosphate and the related compounds rubidium titanyl phosphate (RbTiOPO4) and potassium titanyl arsenate (KTiOAsO4) based on density functional theory and compared them with experimental data. Overall, this allows us to assign various spectral features to eigenmodes of lattice substructures with improved detail compared to previous assignments. Nevertheless, the analysis also shows that not all features of the spectra can unambigiously be explained yet. A possible explanation might be that defects or long range fields not included in the modeling play a crucial rule for the resulting Raman spectrum. In conclusion, this work provides an improved foundation into the vibrational properties in the KTiOPO4 material family.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science; General Chemical Engineering

Solid solutions of lithium niobate and lithium tantalate: crystal growth and the ferroelectric transition - Bashir, Umar; Böttcher, Klaus; Klimm, Detlef; Ganschow, Steffen; Bernhardt, Felix; Sanna, Simone; Rüsing, Michael; Eng, Lukas M.; Bickermann, Matthias (Ferroelectrics)
Specific heat capacity measurements by differential scanning calorimetry (DSC) of single crystals of solid solutions of LiNbO3 and LiTaO3 are reported and compared with corresponding ab initio calculations, with the aim to investigate the variation of the ferroelectric Curie temperature as a function of composition. For this purpose, single crystals of these solid solutions were grown with Czochralski pulling along the c-axis. Elemental composition of Nb and Ta was investigated using XRF analysis, and small samples with homogeneous and well known composition were used for the DSC measurements. We observed that the ferroelectric Curie temperature decreases linearly with increasing Ta concentration in the LiNb1−x Tax O3 solid solution crystals. Furthermore, the ferroelectric transition width of a mixed crystal appears to be smaller, as compared to pure LiTaO3.
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Learning the pronunciation of segmental features of english phonology at german primary schools - Hahn, Charlotte Anna
In der vorliegenden Arbeit wird die Auswirkung expliziter Ausspracheübungen auf die englische Aussprache von Kindern an Grundschulen in NRW untersucht. Das Ziel dieser Arbeit ist es, eine Alternative für den mittel-offenen vorderen Vokal /æ/ und die dentalen Frikative /, ð/ zu bieten. Es wurde eine Interventionsstudie mit 72 Teilnehmenden aus drei verschiedenen Grundschulklassen durchgeführt; zwei vierte Klassen mit verschiedenen Lehrkräften und eine dritte Klasse, die von der Lehrperson einer der vierten Klassen unterrichtet wurde. Jede Klasse wurde in eine Kontroll- und zwei Interventionsgruppen (je eine für den Vokal und die Konsonanten) geteilt. Alle Gruppen wurden einmal zu Beginn und zwei Mal am Ende der Studie getestet. Zwischen den letzten beiden Tests lagen sechs bis acht Wochen, um einen mittelfristigen Effekt zu testen. Die Intervention, die nach der ersten Messung stattfand, wurde auf zwei je ca. drei-minütige Einzelsitzungen aufgeteilt. Während der Intervention übten die Teilnehmenden mit der Autorin die Aussprache des relevanten Phonems. Die Ergebnisse dieser Studie zeigen, dass die Interventionen einen Effekt auf die Aussprache der Teilnehmenden hatten. Wie sich dieser Effekt verhält und entwickelt scheint von der Art des Phonems, dem Alter der Teilnehmenden sowie der bisherigen Ausspracheschulung abzuhängen. Die vorliegenden Ergebnisse liefern Erkenntnisse nicht nur für die Grundschule selbst, sondern auch für die Lehrer*innenausbildung und Lehrplanentwicklung.

Vorzeichenrichtige tomographische Rekonstruktion von Ultraschallfeldern mit Hilfe der Schlierentechnik - Hetkämper, Tim; Claes, Leander; Henning, Bernd (tm - Technisches Messen)
Keywords: Electrical and Electronic Engineering; Instrumentation

Systematics for an Integrative Modelling of Product and Production System - Schäfer, Louis; Günther, Matthias; Martin, Alex; Lüpfert, Mariella; Mandel, Constantin; Rapp, Simon; Lanza, Gisela; Anacker, Harald; Albers, Albert; Köchling, Daniel (Procedia CIRP)
Keywords: General Medicine

Virtual Assembly for Engineering – A Systematic Literature Review - Dyck, Florian; Anacker, Harald; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Reibungsinduzierter Prozess zum nutzerindividuellen und energieeffizienten Recycling von Aluminiumschrotten - Borgert, Thomas
Die weltweit erzeugten Emissionen müssen in allen emittierenden Sektoren signifikant gesenkt werden, um die Auswirkungen des Klimawandels zu reduzieren. Dies ist unter anderem durch die energieeffiziente Wiederverwertung vorhandener Ressourcen und damit der Einstellung einer nachhaltigen Kreislaufwirtschaft möglich. Aufgrund der hohen erforderlichen Energiemenge in der primären Herstellung von Aluminium existieren hier im Vergleich zu anderen Konstruktionswerkstoffen große Einsparpotentiale. Mit dem in dieser Arbeit erforschten reibungsinduzierten Recyclingverfahren (RIR) wird eine alternative und energieeffiziente Prozessroute zum direkten Recycling von unterschiedlichen Aluminiumschrotten geschaffen. Zur Charakterisierung der Prozessroute werden u. a. die Erkenntnisse aus sich gegenseitig unterstützenden experimentellen und theoretischen Untersuchungen zu den Vorgängen der der Verdichtung, Plastifizierung als auch Extrusion der recycelten Profile dargelegt. Die Einflüsse unterschiedlicher Eingangsgrößen wie z. B. der Werkzeuggestaltung oder der Verarbeitung unterschiedlicher Legierungen werden zudem zur zukünftigen Auslegung des Prozesses erläutert. Aus der abschließenden energetischen Bilanzierung kann geschlossen werden, dass aufgrund der geringeren Verarbeitungstemperatur signifikante Energieersparnisse bei Verwendung des RIR im Vergleich zu den konventionellen Produktionsstrategien erzielt werden können.

Kinderladenbewegung: Auf den Spuren von Kinderladenkindern und ihren Eltern zwischen Laden, Garten und Natur. - Göddertz, Nina; Bock, Karin (Handbuch Kindheit, Ökologie, Nachhaltigkeit)

Kindermädchen – Von ‚strebsamen Mädchen‘, fliegenden Regenschirmen und neuen Gewändern eines (nicht) ausgestorbenen Berufes - Göddertz, Nina (Soziale Frauenberufe in Ost und West)

Dienstmädchen – von romantisierten Zuschreibungen und menschenunwürdigen Arbeits- und Lebensbedingungen, damals wie heute. - Göddertz, Nina (Soziale Frauenberufe in Ost und West)

Ein ‚bunter Blumenstrauß‘ an Praxisphasen. Gestaltungsaufgaben und Entwicklungsbedarfe in der Lehrer*innenbildung Sozialpädagogik. - Göddertz, Nina; Schmoekel, Michelle Jaquelina (Berufsbildung. Zeitschrift für Theorie-Praxis-Dialog)

The Choice of Ideology and Everyday Decisions - Burs, Carina; Gries, Thomas; Müller, Veronika (Journal of Organizational Psychology)
Individuals strive to make decisions that are consistent with not only their consumer preferences but also their psychological needs. However, they are confronted with complex, ambiguous or even false information. Ideologies and belief systems provide guidance when processing and evaluating information and give a coherent and comprehensible interpretation of reality. The first question is: why is an individual attracted to a particular ideology? Individuals choose ideologies that resonate with their subjective psychological needs and preferences. Second, how do individuals search for ideologies and find out which suit them best? We model an individual’s sequential information search for the best matching ideologies by applying Bayesian learning and utility optimization. Additional information enhances utility by reducing uncertainty. As a search is costly, the process may stop once an individual adopts an ideology even if the information set remains incomplete. Third, once they have chosen a particular ideology, individuals adhere to its rules and norms when making everyday decisions. Consumers not only physically consume, but they also act in accordance with their psychological needs.
Keywords: Economics; Ideology; Decision-making

Erlebnisorientiert Lehren und Lernen in der beruflichen Bildung. Entwicklung eines didaktischen Konzepts im Rahmen von designbasierter Forschung. - Volgmann, Simone

Minisymposium Data Science - Podworny, Susanne; Frischemeier, Daniel (Beiträge zum Mathematikunterricht 2022: 56. Jahrestagung der Gesellschaft für Didaktik der Mathematik vom 29.08.2022 bis 02.09.2022 in Frankfurt am Main)

Wege zu einer Didaktik der Sozialpädagogik
Wie kann sozialpädagogisches Handeln erlernt und gelehrt werden? Die Qualifizierungswege für sozialpädagogische Fachkräfte sind vielfältig, mitunter widersprüchlich und in verschiedenen Ebenen eingelagert, von Berufsfachschulen, Fachschulen, Fachhochschulen bis hin zu universitären Studiengängen. Ebenso vielfältig sind die beruflichen Anforderungen an sozialpädagogische Fachkräfte. Der Sammelband widmet sich den unterschiedlichen Zugängen zu einer Didaktik der Sozialpädagogik in Bezug auf die Bildungs-, Lern- und Qualifizierungsprozesse zukünftiger sozialpädagogischer Fachkräfte sowie Lehramtsstudierender mit der beruflichen Fachrichtung Sozialpädagogik.
Keywords: Ausbildung Kita-Fachkraft; Ausbildung Soziale Arbeit; Care-Berufe; didaktische Grundlagen; Erzieher*innen-Ausbildung; Erzieher-Ausbildung; Fachkräftemangel; Fachrichtung Sozialpädagogik; Lehramt Sozialpädagogik; schulische Ausbildung; soziale Berufe; Sozialpädagogik unterrichten; Sozialpädagogische Ausbildungsgänge; Sozialwesen; Unterricht Soziale Arbeit

A Social Network Approach for Investigating Social Influences on Effective Use: Demonstration in Virtual Reality Collaboration - Tölle, Laura; Slawinski, Elena; Fromm, Jennifer; Mirbabaie, Milad

Under Pressure? - The Effect of Conversational Agents on Task Pressure and Social Relatedness in Digital Labor - Lichtenberg, Sascha; Hildebrandt, Fabian; Mirbabaie, Milad

Understanding Digital Nomadism as an Employer Branding Signal - Marx, Julian; Langer, Marie; Mirbabaie, Milad

Model Predictive Direct Self-Control for Six-Step Operation of Permanent-Magnet Synchronous Machines - Pena, Mario; Meyer, Michael; Wallscheid, Oliver; Böcker, Joachim (IEEE Transactions on Power Electronics)
Keywords: Electrical and Electronic Engineering

Differentially Private Natural Language Models: Recent Advances and Future Directions

How Much User Context Do We Need? Privacy by Design in Mental Health NLP Applications - Sawhney, Ramit; Neerkaje, Atula; Habernal, Ivan; Flek, Lucie (Proceedings of the International AAAI Conference on Web and Social Media)
Clinical NLP tasks such as mental health assessment from text, must take social constraints into account - the performance maximization must be constrained by the utmost importance of guaranteeing privacy of user data. Consumer protection regulations, such as GDPR, generally handle privacy by restricting data availability, such as requiring to limit user data to 'what is necessary' for a given purpose. In this work, we reason that providing stricter formal privacy guarantees, while increasing the volume of user data in the model, in most cases increases benefit for all parties involved, especially for the user. We demonstrate our arguments on two existing suicide risk assessment datasets of Twitter and Reddit posts. We present the first analysis juxtaposing user history length and differential privacy budgets and elaborate how modeling additional user context enables utility preservation while maintaining acceptable user privacy guarantees.

One size does not fit all: Investigating strategies for differentially-private learning across NLP tasks - Senge, Manuel; Igamberdiev, Timour; Habernal, Ivan (Proceedings of the 2022 Conference on Empirical Methods in Natural Language Processing)

DP-BART for Privatized Text Rewriting under Local Differential Privacy - Igamberdiev, Timour; Habernal, Ivan (Findings of the Association for Computational Linguistics: ACL 2023)

The Legal Argument Reasoning Task in Civil Procedure - Bongard, Leonard; Held, Lena; Habernal, Ivan (Proceedings of the Natural Legal Language Processing Workshop 2022)

Mining legal arguments in court decisions - Habernal, Ivan; Faber, Daniel; Recchia, Nicola; Bretthauer, Sebastian; Gurevych, Iryna; Spiecker genannt Döhmann, Indra; Burchard, Christoph (Artificial Intelligence and Law)
Abstract Identifying, classifying, and analyzing arguments in legal discourse has been a prominent area of research since the inception of the argument mining field. However, there has been a major discrepancy between the way natural language processing (NLP) researchers model and annotate arguments in court decisions and the way legal experts understand and analyze legal argumentation. While computational approaches typically simplify arguments into generic premises and claims, arguments in legal research usually exhibit a rich typology that is important for gaining insights into the particular case and applications of law in general. We address this problem and make several substantial contributions to move the field forward. First, we design a new annotation scheme for legal arguments in proceedings of the European Court of Human Rights (ECHR) that is deeply rooted in the theory and practice of legal argumentation research. Second, we compile and annotate a large corpus of 373 court decisions (2.3M tokens and 15k annotated argument spans). Finally, we train an argument mining model that outperforms state-of-the-art models in the legal NLP domain and provide a thorough expert-based evaluation. All datasets and source codes are available under open lincenses at https://github.com/trusthlt/mining-legal-arguments .
Keywords: Law; Artificial Intelligence

Faktor Mensch. Jahrbuch Technikphilosophie 2023
With the focus topic “The Human Factor”, the Jahrbuch Technikphilosophie 2023 aims to investigate on the one hand the manifold arrangements of the deficiency in the technical field (and especially “new” technologies): How do machine worlds, user interfaces, implementation strategies, or even entire large-scale technological ecosystems model, compensate, and even parody “the” human being – that is, “their” version of ourselves? How does technology discriminate? How does it educate? To what extent can it “reduce” the human? On the other hand, it is necessary to take a new look at what “human” actually means in precisely this context, and to reexamine anthropology as part of theories of technology and discourses on technology. Criticism of technology must therefore also be criticism of man. With contributions by Fabian Anicker, Petra Gehring, Axel Gelfert, Martina Heßler, Andreas Kaminski, Ruth Karl, Katerina Krtilova, Joachim Landkammer, Kevin Liggieri, Felix Maschewski, Nicola Mößner, Anna-Verena Nosthoff, Felix Reda, Jean Paul Sartre, Björn Schembera, Stefan Schöberlein, Marcel Siegler, Florian Sprenger and Martin Warnke.

Protein intake and type 2 diabetes mellitus: an umbrella review of systematic reviews for the evidence-based guideline for protein intake of the German Nutrition Society - Schulze, Matthias B.; Haardt, Julia; Amini, Anna M.; Kalotai, Nicole; Lehmann, Andreas; Schmidt, Annemarie; Buyken, Anette; Egert, Sarah; Ellinger, Sabine; Kroke, Anja; Kühn, Tilman; Louis, Sandrine; et al. (European Journal of Nutrition)
Abstract Purpose Protein-rich foods show heterogeneous associations with the risk of type 2 diabetes (T2D) and it remains unclear whether habitual protein intake is related to T2D risk. We carried out an umbrella review of systematic reviews (SR) of randomised trials and/or cohort studies on protein intake in relation to risks of T2D. Methods Following a pre-specified protocol (PROSPERO: CRD42018082395), we retrieved SRs on protein intake and T2D risk published between July 1st 2009 and May 22nd 2022, and assessed the methodological quality and outcome-specific certainty of the evidence using a modified version of AMSTAR 2 and NutriGrade, respectively. The overall certainty of evidence was rated according to predefined criteria. Results Eight SRs were identified of which six contained meta-analyses. The majority of SRs on total protein intake had moderate or high methodological quality and moderate outcome-specific certainty of evidence according to NutriGrade, however, the latter was low for the majority of SRs on animal and plant protein. Six of the eight SRs reported risk increases with both total and animal protein. According to one SR, total protein intake in studies was ~ 21 energy percentage (%E) in the highest intake category and 15%E in the lowest intake category. Relative Risks comparing high versus low intake in most recent SRs ranged from 1.09 (two SRs, 95% CIs 1.02–1.15 and 1.06–1.13) to 1.11 (1.05–1.16) for total protein (between 8 and 12 cohort studies included) and from 1.13 (1.08–1.19) to 1.19 (two SRs, 1.11–1.28 and 1.11–1.28) (8–9 cohort studies) for animal protein. However, SRs on RCTs examining major glycaemic traits (HbA 1c , fasting glucose, fasting insulin) do not support a clear biological link with T2D risk. For plant protein, some recent SRs pointed towards risk decreases and non-linear associations, however, the majority did not support an association with T2D risk. Conclusion Higher total protein intake was possibly associated with higher T2D risk, while there is insufficient evidence for a risk increase with higher intakes of animal protein and a risk decrease with plant protein intake. Given that most SRs on plant protein did not indicate an association, there is possibly a lack of an effect.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Protein intake and body weight, fat mass and waist circumference: an umbrella review of systematic reviews for the evidence-based guideline on protein intake of the German Nutrition Society - Ellinger, Sabine; Amini, Anna M.; Haardt, Julia; Lehmann, Andreas; Schmidt, Annemarie; Bischoff-Ferrari, Heike A.; Buyken, Anette; Kroke, Anja; Kühn, Tilman; Louis, Sandrine; Lorkowski, Stefan; Nimptsch, Katharina; et al. (European Journal of Nutrition)
Abstract Purpose This umbrella review aimed to assess whether dietary protein intake with regard to quantitative (higher vs. lower dietary protein intake) and qualitative considerations (total, plant-based or animal-based protein intake) affects body weight (BW), fat mass (FM) and waist circumference (WC). Methods A systematic literature search was conducted in PubMed, Embase and Cochrane Database of Systematic Reviews for systematic reviews (SRs) with and without meta-analyses of prospective studies published between 04 October 2007 and 04 January 2022. Methodological quality and outcome-specific certainty of evidence of the retrieved SRs were assessed by using AMSTAR 2 and NutriGrade, respectively, in order to rate the overall certainty of evidence using predefined criteria. Results Thirty-three SRs were included in this umbrella review; 29 were based on randomised controlled trials, a few included cohort studies. In studies without energy restriction, a high-protein diet did not modulate BW, FM and WC in adults in general (all “possible” evidence); for older adults, overall certainty of evidence was “insufficient” for all parameters. Under hypoenergetic diets, a high-protein diet mostly decreased BW and FM, but evidence was “insufficient” due to low methodological quality. Evidence regarding an influence of the protein type on BW, FM and WC was “insufficient”. Conclusion “Possible” evidence exists that the amount of protein does not affect BW, FM and WC in adults under isoenergetic conditions. Its impact on the reduction in BW and FM under hypoenergetic conditions remains unclear; evidence for an influence of protein type on BW, FM and WC is “insufficient”.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Reverberation as Supervision For Speech Separation - Aralikatti, Rohith; Boeddeker, Christoph; Wichern, Gordon; Subramanian, Aswin; Le Roux, Jonathan (ICASSP 2023 - 2023 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

Mixture Encoder for Joint Speech Separation and Recognition - Berger, Simon; Vieting, Peter; Boeddeker, Christoph; Schlüter, Ralf; Haeb-Umbach, Reinhold (INTERSPEECH 2023)

Investigating the potential of artificial intelligence for the employee from the perspective of AI-experts - Humpert, Lynn; Tihlarik, Amelie; Wäschle, Moritz; Anacker, Harald; Dumitrescu, Roman; Albers, Albert; Röbenack, Silke; Pfeifer, Sabine (IEEE International Conference on Technology Management, Operations and Decisions (IEEE ICTMOD))

Identification of fields of action for validation in Systems Engineering - Humpert, Lynn; Zagatta, Kristin; Anacker, Harald; Dumitrescu, Roman (IEEE International Conference on Technology Management, Operations and Decisions (IEEE ICTMOD))

Criteria-based comparison of Systems Engineering and agile methods - Humpert, Lynn; Mundt, Enrik; Bretz, Lukas; Bernz, Vanessa; Anacker, Harald; Dumitrescu, Roman (8th International Conference on Information Systems Engineering)

Strategic planning of the collaboration between humans and artificial intelligence in production - Gabriel, Stefan; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)

Principles for the effective application of Systems Engineering: A systematic literature review and application use case - Mundt, Enrik; Wilke, Daria; Anacker, Harald; Dumitrescu, Roman

Integration von Design Thinking in Systems Engineering mit Hilfe des Systemdenkens - Tekaat, Julian; Wilke, Daria; Anacker, Harald; Dumitrescu, Roman

Lydia Böttger (Universität Paderborn) rezensiert: Burwitz-Melzer, Eva; Riemer, Claudia; Schmelter, Lars (Hrsg.) (2022): Feedback beim Lehren und Lernen von Fremd- und Zweitsprachen. Arbeitspapiere der 42. Frühjahrs- konferenz zur Erforschung des Fremdsprachenunterrichts. [Giessener Beiträge zur Fremdsprachendidaktik]. Tübingen: Narr Francke Attempto, 245 Seiten. ISBN 978-3- 8233-8569-1 - Böttger, Lydia (www.daz-portal.de)

Alignment between timing of ‘highest caloric intake’ and chronotype in relation to body composition during adolescence: the DONALD Study - Jankovic, Nicole; Schmitting, Sarah; Stutz, Bianca; Krüger, Bettina; Buyken, Anette; Alexy, Ute (European Journal of Nutrition)
Abstract Purpose Our aim was to assess alignment in timing of ‘highest caloric intake’ with individual chronotype and its association with body composition in adolescents. Methods We used repeatedly collected data from n = 196 adolescents (age 9–16 years, providing N = 401 yearly questionnaires) of the DONALD open cohort study. Chronotype was assessed by the Munich Chronotype Questionnaire from which midpoint of sleep (MSFsc) was derived. A sex- and age-specific diet-chrono-alignment score (DCAS) was calculated as the difference in hours between the chronotype-specific median timing of highest caloric intake of the studied population and the individual timing of ‘highest caloric intake’ or vice versa. Repeated-measures regression models were applied to study cross-sectional and longitudinal associations between the DCAS and body composition, e.g., Fat Mass Index (FMI) or Fat Free Mass Index (FFMI). Results DCAS ranged from −6:42 h to + 8:01 h and was not associated with body composition. Among adolescents with a later chronotype ( N = 201) a 1 h increase in DCAS (later consumption of ‘highest caloric intake’ in comparison to the median intake of that group), increased FFMI by 1.92 kg/m 2 (95% CI: 0.15, 3.69, p value = 0.04) over a median follow-up of 0.94 year. Conclusion Alignment of energy intake with individual chronotype appears beneficial for FFMI among those with a late chronotype.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Re-examining the quality dimensions of synthetic speech - Seebauer, Fritz; Kuhlmann, Michael; Haeb-Umbach, Reinhold; Wagner, Petra (12th Speech Synthesis Workshop (SSW) 2023)

Verben in Szenen. Grammatikgespräche im Sprachvergleich - Topalović, Elvira; Blachut, Alisa (Grundschule Deutsch)

Professionelle Unterrichtswahrnehmung von Lehramtsstudierenden – das Projekt iDEAL. Vortrag auf der Herbsttagung 2023 der Arbeitsgruppe Empirische Sonderpädagogische Forschung (AESF) - Görel, Gamze; Finke, Pauline; Hellmich, Frank

Breaking Down Barriers: How Conversational Agents Facilitate Open Science and Data Sharing - Mirbabaie, Milad; Rieskamp, Jonas; Hofeditz, Lennart; Stieglitz, Stefan

From Virality to Veracity: Examining False Information on Telegram vs. Twitter - Rieskamp, Jonas; Mirbabaie, Milad; Langer, Marie; Kocur, Alexander

Practice reduces the costs of producing head fakes in basketball - Böer, Nils Tobias; Weigelt, Matthias; Schütz, Christoph; Güldenpenning, Iris (Psychological Research)
Abstract Previous research indicates that performing passes with a head fake in basketball leads to increased response initiation times and errors as compared to performing a pass without a head fake. These so-called fake production costs only occurred when not given the time to mentally prepare the deceptive movement. In the current study, we investigated if extensive practice could reduce the cognitive costs of producing a pass with head fake. Twenty-four basketball novices participated in an experiment on five consecutive days. A visual cue prompted participants to play a pass with or without a head fake either to the left or right side. The cued action had to be executed after an interstimulus interval (ISI) of either 0 ms, 400 ms, 800 ms or 1200 ms, allowing for different movement preparation times. Results indicated higher response initiation times (ITs) and error rates (ERs) for passes with head fakes for the short preparation intervals (ISI 0 ms and 400 ms) on the first day but no difference for the longer preparation intervals (ISI 800 ms and 1200 ms). After only one day of practice, participants showed reduced fake production costs (for ISI 0 ms) and were even able to eliminate these cognitive costs when given time to mentally prepare the movement (for ISI 400 ms). Accordingly, physical practice can reduce the cognitive costs associated with head-fake generation. This finding is discussed against the background of the strengthening of stimulus response associations.
Keywords: Arts and Humanities (miscellaneous); Developmental and Educational Psychology; Experimental and Cognitive Psychology; General Medicine

Die Bedeutung digitaler Medien für die unterrichtsbezogene Lehrerkooperation - erste Ergebnisse einer empirischen Studie - Engemann, Mario; Herzig, Bardo

Accelerating the analysis of optical quantum systems using the Koopman operator - Peitz, Sebastian; Hunstig, Anna; Rose, Hendrik; Meier, Torsten
The prediction of photon echoes is an important technique for gaining an understanding of optical quantum systems. However, this requires a large number of simulations with varying parameters and/or input pulses, which renders numerical studies expensive. This article investigates how we can use data-driven surrogate models based on the Koopman operator to accelerate this process. In order to be successful, we require a model that is accurate over a large number of time steps. To this end, we employ a bilinear Koopman model using extended dynamic mode decomposition and simulate the optical Bloch equations for an ensemble of inhomogeneously broadened two-level systems. Such systems are well suited to describe the excitation of excitonic resonances in semiconductor nanostructures, for example, ensembles of semiconductor quantum dots. We perform a detailed study on the required number of system simulations such that the resulting data-driven Koopman model is sufficiently accurate for a wide range of parameter settings. We analyze the L2 error and the relative error of the photon echo peak and investigate how the control positions relate to the stabilization. After proper training, the dynamics of the quantum ensemble can be predicted accurately and numerically very efficiently by our methods.

An IAD framework analysis of minigrid institutions for sustainable rural electrification in East Africa: A comparative study of Uganda and Tanzania - Namujju, Lillian Donna; Acquah-Swanzy, Henrietta; Ngoti, Irene F. (Energy Policy)
Keywords: Management; Monitoring; Policy and Law; General Energy

Thermo-hydraulic Performance of Pillow-Plate Heat Exchangers with Secondary Structuring: A Numerical Analysis - Afsahnoudeh, Reza; Wortmeier, Andreas; Holzmüller, Maik; XGong, Yi; Homberg, Werner; Kenig, Eugeny Y. (Energies)

Sure you are ready? Gendered arguments in recruitment for high-status positions in male-dominated fields - Dutz, Regina; Hubner-Benz, Sylvia; Emmerling, Franziska; Peus, Claudia (Frontiers in Psychology)
Recruitment contexts such as STEM professorships promote clearly defined selection criteria and objective assessment. We illuminate in these contexts, the subjective interpretation of seemingly objective criteria and gendered arguments in discussions of applicants. Additionally, we explore gender bias despite comparable applicant profiles investigating how specific success factors lead to selection recommendations for male and female applicants. Implementing a mixed methods approach, we aim to highlight the influence of heuristics, stereotyping, and signaling in applicant assessments. We interviewed 45 STEM professors. They answered qualitative open-ended interview questions, and evaluated hypothetical applicant profiles, qualitatively and quantitatively. The applicant profiles enabled a conjoint experiment with different applicant attributes varied across the profiles (i.e., publications, willingness to cooperate, network recommendation, and applicant gender), the interviewees indicating scores of selection recommendation while thinking aloud. Our findings reveal gendered arguments, i.e., questioning women potentially fueled by a perception of women’s exceptional status and perceived self-questioning of women. Furthermore, they point to gender-independent and gender-dependent success patterns, thereby to potential success factors particularly for female applicants. We contextualize and interpret our quantitative findings in light of professors’ qualitative statements.
Keywords: General Psychology

Robot leadership–Investigating human perceptions and reactions towards social robots showing leadership behaviors - Cichor, Jakub Edward; Hubner-Benz, Sylvia; Benz, Tobias; Emmerling, Franziska; Peus, Claudia (PLOS ONE)
Human-robot interaction research has shown that social robots can interact with humans in complex social situations and display leadership-related behaviors. Therefore, social robots could be able to take on leadership roles. The aim of our study was to investigate human followers’ perceptions and reactions towards robot leadership behavior, and differences based on the robot’s displayed leadership style. We implemented a robot to show either a transformational or a transactional leadership style in its speech and its movements. We presented the robot to university and executive MBA students (N = 29) and subsequently conducted semi-structured interviews and group discussions. The results of explorative coding indicated that participants differed in their perceptions and reactions based on the robot’s leadership style and based on their assumptions about robots in general. We observed that participants quickly imagined either a utopia or worried about a dystopia, depending on the robot’s leadership style and their assumptions, and that a subsequent reflection led to more nuanced views. We discuss the implications and recommendations for human-robot interaction and leadership research.
Keywords: Multidisciplinary

What predicts effectuation preferences Disentangling individual and environmental factors and illuminating decision criteria - Hubner-Benz, Sylvia; Baum, Matthias (International Journal of Entrepreneurial Venturing)
Keywords: Management of Technology and Innovation; Strategy and Management; Business and International Management

Different ways lead to ambidexterity: Configurations for team innovation across China, India, and Singapore - Deng, Wei; Hubner-Benz, Sylvia; Frese, Michael; Song, Zhaoli (Journal of International Management)
Keywords: Strategy and Management; Finance; Business and International Management